Clays and Clay Minerals, Vol. 56, No. 6, 730–750, 2008. - Meunier, Alain; Mas, Antoine; Beaufort, Daniel; Patrier, Patricia; Dudoignon, Patrick (The Clay Minerals Society, 2008)
The clay minerals formed in chilled margins and massive crystallized inner parts of three basalt-hawaiite bodies of Mururoa Atoll (French Polynesia) exhibit contrasting textures. Glass alteration textures are observed around fractures crosscutting the quenched margins: Fe-rich clays grow inward into the glass (retreating surface) while Mg-rich clays grow outward (open space). The textures of clay deposits filling the diktytaxitic voids (mesostasis) in the massive inner parts of the three volcanic bodies are different: unoriented clay matrix with embedded euhedral apatite and pyroxene microcrysts (submarine flow); pallisadic clays coating the void walls and the crystal surfaces of apatite and K-feldspar microcrysts (subaerial flow); and clay muffs covering all the apatite needles, with the central part of the void remaining empty (dike). The unoriented texture could result from the alteration of a glass precursor concomitant with the olivine phenocrysts (clay pseudomorphs). However, such an alteration implies important chemical transfers which are not observed. The pallisadic and muff textures form through heterogeneous nucleation on the solid surfaces and crystal growth from a saline solution. No glass precursor existed. As the center of the diktytaxitic voids in the dike is empty, the residual liquid was probably boiling. The amounts of light rare earth elements (LREE), Sr, and the most incompatible elements are greater in clays from diktytaxitic voids relative to the amounts formed in the altered glass of the chilled margins. Thus, diktytaxitic clays formed from a residual liquid which gave either an evolved glass or a saline solution after cooling (fractionation process). The d18O var iation vs. loss on ignition (LOI) indicates that sea waterwa s involved either in rock alteration or magma contamination. This is confirmed by the 87Rb/86Sr ratio of bulk rocks and clay fractions from the quenched and massive inner parts of the three volcanic bodies which do not fit with the 11.5Ma isochron indicating that the Rb-Sr system was not closed at any stage during the magmatic history.
Clay Minerals In Basalt-hawaiite Rocks From Mururoa Atoll (french Polynesia). Ii. Petrography And Geochemistry
gsccm56612-meu.pdf - 1,894KB
Keywords: Periodicals; Geology; Basalt Alteration; Diktytaxitic Void; French Polynesia; Isotopes; Mesostasis Texture; Mururoa Atoll